ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMELS DAN RGEC PADA PT. BANK XXX PERIODE 2008-2011 - Angrawit Kusumawardani (Universitas Gunadarma, 2015)
This study aims to determine the level of health in the PT. Bank XXX when measured using the method CAMELS (Capital, Assets, Management, Earnings, Liquidity, Sensitivity to Market Risk) in 2008-2011. And also aims to determine differences in the ratios used in the method and the method CAMELS RGEC. The results showed healthy banks can be said for almost all ratios are used to qualify specified. In the CAMELS method is not all ratios reuse on RGEC method. The same indicator only on Capital and Earnings. While other indicators on CAMELS not used anymore or forming a new indicator on RGEC. Keyword: CAMELS, RGEC, Capital, risk, Asset